Estrategia psicoeducativa basada en la música clásica para disminuir las conductas agresivas del tercer curso de bachillerato paralelo A ,de la unidad educativa Pio Jaramillo Alvarado, 2019-2020. - Córdova Curimilma, Bryan Efrén (2020)
The contemplation of violence is an important problem worldwide, causing physical and psychological damage, both individual and social; Therefore, this research is about: PSYCHOEDUCATIONAL STRATEGY BASED ON CLASSIC MUSIC TO REDUCE AGGRESSIVE BEHAVIORS OF THE THIRD COURSE OF HIGH SCHOOL PARALLEL A OF THE EDUCATIONAL UNIT PIO JARAMILLO ALVARADO, 2019-2020; The general objective was formulated: To apply the psychoeducational strategy based on classical music to reduce the manifestations of aggressive behaviors of the Third Year of Parallel A High School of the Pio Jaramillo Alvarado Educational Unit, in such a way that these psychoeducational strategies are used frequently in their daily life. The research design was descriptive, cross-sectional and quasi-experimental; based on the methods: scientific, inductive, deductive, analytical, synthetic, historical, comprehensive, diagnostic, modeling and statistical of the linear correlation coefficient of Karl Pearson (r). In addition, the AQ aggressiveness questionnaire by Buss and Perry was used, applied to a sample of 23 students from the third year of high school A. The pre-test results at the very high level show hostility (8.70%), verbal aggressiveness (13.04%), anger (4.35%) and physical aggression (4.35%). Later, in the post-test where it is evident that at the very high level there is a decrease in hostility (4.35%), verbal aggressiveness (4.35%), anger (0.00%) and physical aggressiveness (0.00%). ). In this way, the aggressive behavior factors are found at high and medium levels, due to which the aggressiveness levels decreased satisfactorily, achieving an adequate learning environment.